Study guides

Q: P 2x-9y q 5y plus 6-4x r 3x plus 3y-5 then p plus q plus r?

Write your answer...

Submit

Related questions

4. 12x^2-64x-256=4(3x^2-16x-64)

6x2 + 64x - 12 = 10 ∴ 6x2 + 64x - 22 = 0 ∴ 3x2 + 32x - 11 = 0 ∴ 3x2 + 33x - x - 11 = 0 ∴ 3x(x + 11) - 1(x + 11) = 0 ∴ (3x - 1)(x + 11) = 0 ∴ x ∈ {1/3, -11}

No. It is 9x, which is a monomial.

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

6x plus 8

3x plus 2y can be expressed mathematically as (3x + 2y).

3x-3x+4x^2+8x=4x^2+8x

3x + 11

50, 53, 59

6x + 8

I think you mean (3x ± 1)^2 = (3x+1)(3x-1)?

The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.

It is equivalent to: 3x+6+5 = 3x+11

3x + 2 = 3x + 6 This is not possible.

It is: 3x+10y+5 simplified

The Abelian property or commutativity.

6x

The sum of 3x plus 2 and -4 plus 3 is 3x+1 if the equation is (3x+2)+(-4+3). If they are two separate questions, 3x+2 remains as itself while -4+3=-1.

9x2 + 6x + 1 = 9x2 + 3x + 3x + 1 = 3x(3x + 1) + 1(3x + 1) = (3x + 1)(3x + 1) or (3x +1)2

3x + y

-3x + 1

9x+3

The answer is y = -3x -4.

3x + 6y + 6x = 9x + 6y which can be factorised as 3(3x +2y)

38*4 + 3 + 7 - 3x = 162 - 3x